Delivery of LINC00589 via mesoporous silica nanoparticles inhibits peritoneal metastasis in gastric cancer. (28th November 2022) - Wang, Shuchang; Wo, Lulu; Zhang, Zizhen; Zhu, Chunchao; Wang, Chaojie; Wang, Yangyang; Hou, Lechun; Cao, Hui; Zhao, Qian; Zhao, Enhao
Abstract: Peritoneal metastasis is one of the common forms of metastasis in gastric cancer (GC). In this study, we identified the expression pattern of LINC00589 in GC patients and investigate the biological function in GC cells. RNA-pulldown assay was performed to explore the underlying molecular mechanism. Further, we utilize polyethyleneimine-modified mesoporous silica nanoparticles (PMSNs) as the nanocarriers for delivery of LINC00589 encoding plasmid and tested its therapeutic potential for GC with peritoneal dissemination. We revealed that LINC00589 was downregulated in GC tissues and suppressed the metastatic ability of GC cells. Mechanistically, LINC00589 exerted tumor suppressive function by promoting hnRNPA1 protein ubiquitination and proteasomal degradation, thus blocking alternative splicing of PKM to PKM2. Furthermore, LINC00589 delivered by PMSNs could suppress the peritoneal metastasis of GC in vivo and in vitro . This work may provide a new treatment option in GC peritoneal metastasis. Highlights: LINC00589 is downregulated in GC tissues and is relevant to prognosis. LINC00589 suppresses the migration and invasion of GC cells . LINC00589 physically interacting with hnRNPA1 in GC cells. LINC00589 exerts its function through hnRNPA1/PKM axis in GC cells. LINC00589 delivered by PMSNs suppress peritoneal metastasis in vitro and in vivo.